SISTEM INFORMASI PENJUALAN MENU MAKANAN PADA WARTEG BAHARI BERBASIS WEB MENGGUNAKAN METODE WARTERFALL - Bagas Gilang Sudrajat; Arief Maulana Thamrin; Roeslan Djutalov (CV. Multi Kreasi Media, 2023)
Warung Tegal, also known as Warteg, is a type of food stall that is widely known by the people of Indonesia, especially among the lower middle class. Cheap prices and simple presentation are characteristics that are the main factors why Warung Tegal is more attached to these communities. The development of information systems is now very fast and rapid, not a few use information systems to help ease work. The system development method used in making this information system uses the Waterfall Model. The research objective of making a website at this maritime warteg is to provide convenience for customers or buyers in terms of obtaining information about the products provided and product updates can be carried out quickly and can be known on time by customers. Completion of the results of this study with the application of a website-based maritime warteg sales information system, can make it easier for buyers and customers to place orders at warteg and can make it easier to make sales in managing and reporting sales data.